Transcriptional activation of elephant shark mineralocorticoid receptor by corticosteroids, progesterone, and spironolactone - Yoshinao Katsu; Satomi Kohno; Kaori Oka; Xiaozhi Lin; Sumika Otake; Nisha E. Pillai; Wataru Takagi; Susumu Hyodo; Byrappa Venkatesh; Michael E. Baker (2019)
Binding and activity assays suggest a role for progesterone in stimulating the elephant shark mineralocorticoid receptor.